MATCHING CONFIGURATIONS PROJECTS OF COOPERATIVE MILK COLLECTION PROJECT ENVIRONMENT - Анатолій Миколайович ТРИГУБА; Андрій Остапович ШАРИБУРА; Петро Васильович ШОЛУДЬКО; Микола Віталійович РУДИНЕЦЬ (Вісник Національного технічного університету «ХПÌ». Серія: Стратегічне управління, управління портфелями, програмами та проектами, 2017)
The condition analysis of dairy farming is done and the reasons for its degradation are revealed. The need of technologically integrated production systems projects, harvesting, and processing of milk are substantiated. A scientific methodology and the method of project design of milk provision cooperative coordination in the community of the project environment, which are based on systematic-evaluative approach and simulation are proposed. The criterion for the definition of rational parameters of objects configuration for milk provision cooperative projects in the community system is the maximum value of their product. The monetary functioning assessment of the configuration object of cooperative milk provision projects in the community is done. On the basis of the proposed method, we performed the coordination of project configuration of milk provision cooperative with the project environment of territory Zabolotsi community in Brody district of Lviv region.